La bolsa de valores de Colombia, su naturaleza y su posición sobre las sociedades comisionistas de bolsa: el planteamiento del Service Level Agreement (SLA) como posible forma de mitigación - Rodríguez Rodríguez, Néstor David (2018)
Stock exchanges are vital agents for capital market development and the stock market of a country. This article defines «stock exchange» in Colombia and analyzes its characteristics from a legal, financial and market point of view. Furthermore, this article reviews the contractual relationship between the Colombian Stock Exchange and the market agents, especially with the Colombian Stock Brokerage Firms, in order to conclude the existence of both dominant position and a monopoly that favors the Colombian Stock Exchange. Finally, the «Service Level Agreement» is proposed as a way to alleviate both the monopoly and dominant position’s effects of the Colombian Stock Exchange. For the relevant purposes, this article was developed by using the dogmatic-legal investigation, jurisprudential, and legal analysis method, and through the use of methodological, descriptive, comparative and propositional tools.